PROSES PELAJARAN SEJARAH KEBUDAYAAN ISLAM SISWA KELAS IX DAN DAMPAKNYA TERHADAP PENGETAHUAN SEJARAH AGAMA ISLAM DI INDONESIA PADA MTs AR RIDHO MEDAN - Supriadi, Supriadi (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
The aim of this research is to find out the impact of studying the History of Islamic Culture at Madrasah Tsanawiyah Ar Ridha on knowledge of the history of the Islamic religion in Indonesia. The type of research that I will use in this research is descriptive qualitative which emphasizes the use of field data. Then the data comes from the research location, the existing reality, directly by the researcher and is in accordance with conditions in the field, describing all the conditions that existed at the time of the research. The research carried out obtained results using a qualitative approach and data collection techniques using observation, interviews and documentation in the field regarding learning the History of Islamic Culture at MTs Ar Ridho Medan experiencing several obstacles, including the obstacles experienced in learning the History of Islamic Culture, namely the background of the participants. different students, lack of facilities and infrastructure to support the teaching and learning process of Islamic Cultural History. as well as, limited time for teaching Islamic Cultural History lessons.